Calculation of blast area for acute leukemia blood cells images - Nor Hazlyna, Harun; Mohd Yusoff, Mashor, Prof. Dr.; Rosline, Hassan, Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.